Determination of pKa and Thermodynamic Data of Some Schiff Bases Derived From 4,6-Dimethyl 2-Amino Pyrimidine - Aziz, H. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Acid dissociation constants of some Schiff bases derived from 4, 6-dimethyl 2-amino pyrimidine of the type (1) in 50% V/V dioxane-water mixture in 0.003M KCl, at three different temperatures were determined potentiometrically. The thermodynamic energies were calculated and a good linear correlation was obtained between pKa and IR OH. Stretching frequencies.